Genome-wide association analysis implicates dysregulation of immunity genes in chronic lymphocytic leukaemia - Philip J. Law (Nature Portfolio, 2017)
Chronic lymphocytic leukaemia has a hereditary component, much of which remains to be identified. Here, the authors perform a genome-wide association study and find new risk loci for the disease, which are associated with genes involved in immune function.